Transformation of Story Structure and Shifting Values in Western Early Childhood Literature: A Study of The Works of Beatrix Potter and Eric Carle - Rizano, Gindho; Sandika, Edria (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2026)
Beatrix Potter and Eric Carle are two of the great children’s literature writers, representing two different periods and two different nations (The United States and England) related by the English language. Using a conventional structuralist point of view, this article explores two basic structures that each of the author uses in their books. It also seeks to show two different sets of values that each author promotes, shedding light on shifts of values that have been shaping the lives of English-speaking people.